Numerical analysis of laser transmitter nonlinearity compensation technique for radio over fiber system - Neo, Y. S. (John Wiley & Sons, Ltd., 2011)
The task of reducing the noise and distortion generated by a laser transmitter has always been a challenge to improve the performance of radio over fiber systems. This paper presents a compensation system for nonlinear distortion of a laser transmitter supporting 5.2 GHz radio transmission over fiber employing a feed-forward linearization technique. The nonlinearity of the laser diode is modeled using Volterra series analysis. The proposed linearization system is also simulated using commercial optical system software. The novel design has achieved 30 dB nonlinearity reduction considering 800 MHz modulation bandwidth. As an addition, this work also analyzes the effect of transmission length towards distortion reduction of the proposed system.